Comparative evaluation of anticariogenic activity of commercially available herbal dentifrices - Bhargavi Prabhuswamy; Neikar Mallikarjun; Kurni Nagaraj; Basavaraja Simpi (Wolters Kluwer Medknow Publications, 2018)
Background and Aim: Regular use of a potent antiplaque compound, especially formulated in toothpaste, can be beneficial in dental plaque control. Many herbal toothpastes are claiming to have anticariogenic property but they are not evident and not substantiated by the dental professionals. It is important that clinical trials should verify the efficacy of any new product, instead of simply accepting them. Hence, the present work was designed to evaluate and compare the antibacterial activity of commercially available herbal toothpastes against the clinically isolated human Streptococcus mutans. Materials and Methods: The known clinical samples from caries-positive patients were collected, and S. mutans bacteria was isolated and identified by morphology, biochemical profiling, and 16s rDNA sequencing method. The antibacterial efficacy of six herbal toothpastes against S. mutans clinical isolate was evaluated by standard agar well diffusion method. Results: Danthakanthi, among all the tested toothpastes, was found to be more effective with zone of inhibition 27.50 ± 0.51 mm, compared to standard and other tested pastes followed by Miswak and Colgate herbal. Vicco was found to be least effective with zone of inhibition 18.90 ± 0.18 mm against the tested bacteria. Conclusion: Herbal toothpastes have the prospect of becoming safer and effective alternative and provide an ideal home care anticariogenic regime. Toothpaste with multiple herbal ingredients is more efficient than the toothpastes with fewer herbal ingredients in an anticariogenic property.